God’s meaning is love: The mystical theology of Julian of Norwich - P. Sheldrake (Acta Theologica, 2022)
This article focuses on the 14th-century English visionary mystic and theological writer, Julian of Norwich. It suggests that the key to her mystical theology is that a true “knowledge” of God involves loving engagement with God rather than abstract intellectual enquiry. Julian’s reflections on God’s nature, in relation both to her visions of the crucified Christ and to God-as-Trinity, include an exploration of the image of God as mother. Most importantly, Julian struggled for many years to understand the ultimate meaning and purpose of her visions and what God revealed to her through them for the sake of all her fellow Christians. After a long period of challenging reflection and constantly questioning God, Julian is finally led to understand that God’s relationship with humankind is based on love and, indeed, that God’s ultimate meaning is love and only love